Educating Emergency Department Nurses About Miscarriage. Issue 1 (January 2018) - Merrigan, Joyce L.
Abstract : Abstract: Miscarriage is the unwanted ending of a pregnancy before 20 weeks gestation. Women experiencing miscarriage require specialized care from nurses and other healthcare professionals. Many women are dissatisfied with emergency care related to miscarriage and desire honest communication, validation of urgency, and more robust information at discharge. Perinatal bereavement education offers an opportunity for emergency department nurses to acquire specific knowledge and communication skills that assist with understanding the individualized experience of early pregnancy loss. For many women, a miscarriage is devastating, whereas for some, a part of life. Therefore, assessing the meaning of miscarriage is an essential step to providing sensitive, supportive care. Education was offered to emergency department nurses based on a 4-hour Resolve Through Sharing ® curriculum. Education focused on knowledge of policy and practice, medical aspects of pregnancy loss, information on how to assess the meaning of the miscarriage, respectful handling and disposition of the remains, and communication strategies to initiate and sustain a meaningful relationship with the woman and her family, within the barriers to care that are exclusive to the emergency department. Participants embraced the information and actively participated in dialogue of an evaluation process to identify needed revisions in current policies and practices for caring for this patient population. Recommendations and guidance for emergency room nurses who care for women experiencing miscarriage are offered. Abstract : Recommendations for perinatal bereavement education and guidance for clinical practice for emergency department nurses who care for women experiencing miscarriage are offered to assist in understanding the individualized experience of early pregnancy loss and giving compassionate care.